Enhanced Immune Protection of Mud Crab Scylla paramamosain in Response to the Secondary Challenge by Vibrio parahaemolyticus - Zhang, Xin; Zeng, Xinyang; Sun, Yulong; Wang, Yilei; Zhang, Ziping (Frontiers in Immunology, 2020)
“Immune priming” plays a vital part in the immune system of invertebrates against recurrent infections by pathogens, and can provide some ideas for the prevention and treatment of invertebrate diseases. Many invertebrates have been demonstrated recently to have immune priming, but the relevant mechanisms are not known. Expression of immune system-related genes in the hemocytes and hepatopancreas of the mud crab (Scylla paramamosain) before and after repeated stimulation with Vibrio parahaemolyticus were analyzed by real-time fluorescence quantitative polymerase chain reaction. Some molecules that may participate in immune priming of S. paramamosain were screened out, and their possible roles in immune priming were interpreted. Crabs injected first with heat-killed V. parahaemolyticus (HkVp group) or physiologic (0.9%) saline (PS group) were re-challenged at 168 h with live V. parahaemolyticus (HkVp+Vp group and PS+Vp group, respectively). The survival rate of the HkVp+Vp group at 72 h was 20.66% higher than that of PS+Vp group. Expression of genes involved in the toll-like receptor (TLR) signaling pathway and some antimicrobial peptide genes were detected. By respectively comparing gene quantification at different time points in hemocytes and the hepatopancreas, the molecules that may play a part in the early stage of the immune priming of S. paramamosain in the hemocytes were down syndrome cell adhesion molecule (Dscam), Hyastatin, Cactus, Arasin, antilipopolysaccharide factors 3 (ALF3), ALF4, ALF5, and ALF6, and later acting molecules such as Crustin, Dorsal, Pelle, and myeloid differentiation factor 88 (MyD88). The molecules that functioned throughout the entire period were TLR and Spaetzle. In the hepatopancreas, the molecules that may play a part in the early stages of immune priming were Dscam, Hyastatin, Arasin, ALF6, Pelle, Spaetzle, Dorsal and, in the later stage, ALF4. The molecules that functioned throughout the entire period were TLR, Crustin, Cactus, MyD88, and ALF3, ALF5. In summary, the immune function of S. paramamosain was enhanced after it received the same repetitive stimulation by V. parahaemolyticus, indicating immune priming in S. paramamosain. Our study has enriched research on immune priming in invertebrates and laid the foundation for further studies revealing the molecular mechanism of immune priming in crabs.